If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 59 = -1b + -5 Reorder the terms: 59 + b = -1b + -5 Reorder the terms: 59 + b = -5 + -1b Solving 59 + b = -5 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 59 + b + b = -5 + -1b + b Combine like terms: b + b = 2b 59 + 2b = -5 + -1b + b Combine like terms: -1b + b = 0 59 + 2b = -5 + 0 59 + 2b = -5 Add '-59' to each side of the equation. 59 + -59 + 2b = -5 + -59 Combine like terms: 59 + -59 = 0 0 + 2b = -5 + -59 2b = -5 + -59 Combine like terms: -5 + -59 = -64 2b = -64 Divide each side by '2'. b = -32 Simplifying b = -32
| 1/2m-3=2 | | b+59=b-5 | | z-58=-z-8 | | 2x+8=4x+22 | | -a+8=a+98 | | B-56=234 | | -a-9=a+47 | | 4a+5=2a+17 | | (a+4b)+(c-2d)=0 | | 12=22-2x | | 8=3k-3 | | 25+N-100=75 | | 11/20x-1/4x | | 10 x 1/L x 57.8 | | 15.5y+12=12 | | 9x+26=3x+20 | | 4x-3x^3=0 | | 3y+y=72 | | 5x-3x=3+4x | | y=8-x^2-2x | | 8/3:x=4/5:3 | | x+75=2x-20 | | (4+1)*3= | | (2+4)*1= | | 9-3*1= | | N+7n-2=22 | | 2a+2b=86 | | 3-8/4= | | Log(x)+2-2x=0 | | 6/2*3 | | 5+7*6= | | 30r^2-30r=0 |